2016
DOI: 10.1002/adma.201601191
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Red Fluorescent Organic Nanoparticles with Tunable Size and Aggregation‐Induced Emission for Evaluation of Blood–Brain Barrier Damage

Abstract: present safety challenges. Evans blue (EB) assay remains the most commonly used method for the evaluation of BBB damage in the experimental studies of brain injury. [ 7 ] The EB dye works, as widely claimed, based on its ability to bind to serum albumin immediately following its intravenous injection. [ 8,9 ] Although this assay is widely used in numerous studies, EB dye has several limitations as a biomarker, such as its lethal toxicity in vivo and confounding problems in quantitative assessments via various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 51 publications
0
50
0
Order By: Relevance
“…Similarly, it has been demonstrated that 60 nm PS‐PEG particles combined with ultrasound techniques to disturb BBB, can be more diffusive in the normal rat brain than the 110 nm NPs . Furthermore, one study used 10, 30, and 60 nm biocompatible NIR NP; the 10 nm NPs showed poor selectivity, the 30 nm NPs were the most sensitive and selective for BBB damage evaluation, and the 60 nm NPs barely crossed the BBB . In this particular BBB damage imaging/evaluation case, both the 10 and 30 nm NPs can cross the BBB.…”
Section: Physicochemical Properties and Delivery Methods Of Nanocarrimentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it has been demonstrated that 60 nm PS‐PEG particles combined with ultrasound techniques to disturb BBB, can be more diffusive in the normal rat brain than the 110 nm NPs . Furthermore, one study used 10, 30, and 60 nm biocompatible NIR NP; the 10 nm NPs showed poor selectivity, the 30 nm NPs were the most sensitive and selective for BBB damage evaluation, and the 60 nm NPs barely crossed the BBB . In this particular BBB damage imaging/evaluation case, both the 10 and 30 nm NPs can cross the BBB.…”
Section: Physicochemical Properties and Delivery Methods Of Nanocarrimentioning
confidence: 99%
“…B) In vivo fluorescent imaging of PBI mice injected with vehicle alone (PBS) or PSiNPs conjugated with CAQK or CGGK . C) The in vivo images of the brain at 3 h post PTI (a) without NPs administration (b) with 60 nm NPs (c) 30 nm NPs, and (d) 10 nm NPs . D) Bioluminescent images of mice without Dir, with Dir emulsion or DLPAH nanoclusters via tail vein at 12 min after administration .…”
Section: Nanocarriers As Drug Delivery Systemsmentioning
confidence: 99%
“…When the SR expressed on the bEnd.3 cell monolayer was blocked by poly I, the efficient transcytosis of NR@PS‐ b ‐DNA and NR@PS‐ b ‐DNA/Apt was inhibited, resulting in a significantly reduced accumulation in U87MG cells (Figure c and Supporting Information, Figure S6). To study the BBB penetration in vivo, the coronal slices of brains were collected from healthy mice at 3 h post‐injection of NR@PS‐ b ‐DNA and NR@PS‐ b ‐PEG. The CLSM images showed that prominent fluorescence was observed for the NR@PS‐ b ‐DNA group but no fluorescence for the NR@PS‐ b ‐PEG group, resulting in a significant difference in fluorescence intensity (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the proposed method was also adapted for the inspection of microdefects in the bone during the repair process, which required a nondestructive method. The fluorescent signals for both the cracks and defects can be clearly identified in the fluorescence images, which made this method a promising visualization probe for damage detection on the microscale …”
Section: Structure Morphology and Propertiesmentioning
confidence: 98%
“…The fluorescent signals for both the cracks and defects can be clearly identified in the fluorescencei mages, which made this method ap romising visualizationp robe for damage detection on the microscale. [75]…”
Section: Damage Detectionmentioning
confidence: 99%